(untitled) (Ustozlar uchun, 2025)
This article examines the revolutionary role of William Wordsworth and Samuel Taylor Coleridge’s Lyrical Ballads (1798) in shaping English Romantic poetry. The study explores the historical context, the poets’ aesthetic principles, and their redefinition of poetic language and subject matter. Special attention is given to Wordsworth’s theory of “the language of ordinary men” and Coleridge’s concept of the supernatural as complementary approaches within Romanticism. The article concludes that Lyrical Ballads marked a turning point in literary history, giving rise to a new poetic tradition centered on emotion, nature, imagination, and human experience.